Recent topics related to etiology and clinical manifestations of cutaneous arteritis - Ikeda, Takaharu (Frontiers in Medicine, 2022)
Cutaneous polyarteritis nodosa was first reported by Lindberg in 1931. It has been recognized as a skin-limited vasculitis whose cutaneous histopathological features are indistinguishable from those of polyarteritis nodosa. Cutaneous arteritis was defined as a form of single-organ vasculitis in the revised Chapel Hill Classification and was recognized as the same disease as cutaneous polyarteritis nodosa. It became known that deficiency of adenosine deaminase 2 cases were included in cases that had been diagnosed with cutaneous arteritis. Because of their similarity and differences in the treatment methods, deficiency of adenosine deaminase 2 should be considered in cutaneous arteritis cases, especially if they are diagnosed or developed in early childhood. Cutaneous arteritis may be classified as an immune complex-mediated vasculitis. It was reported that the pathogenesis of anti-LAMP-2 antibodies and anti-PS/PT antibodies as good parameters in cutaneous arteritis. The main skin manifestations include livedo racemosa, subcutaneous nodules, and ulcers. Although cutaneous arteritis is recognized to have a benign clinical course, it has become known that it is easy to relapse. The existence of skin ulcers upon diagnosis or sensory neuropathies was suggested to be a predictor of poor prognosis. Cutaneous arteritis with them may need to be treated with more intensive therapies.